A cost-effectiveness analysis of different therapies in patients with chronic hepatitis B in Italy - Giorgio L Colombo; Giovanni B Gaeta; Mauro Viganò et al (Dove Medical Press, 2011)
Giorgio L Colombo1,2, Giovanni B Gaeta3, Mauro Viganò4, Sergio Di Matteo21University of Pavia, School of Pharmacy, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche, Milan, Italy; 3Viral Hepatitis Unit, Second University, Naples, Italy; 4Liver Unit, Ospedale San Giuseppe, Università degli Studi di Milano, Milan, ItalyIntroduction: Chronic hepatitis B (CHB) is a prevalent disease associated with high morbidity, mortality, and impact on health care costs. Antiviral therapy is aimed at reducing hepatitis B virus replication in order to limit progressive liver disease and improve the natural history of the disease. This study estimates the cost-effectiveness of lamivudine, adefovir, telbivudine, entecavir, tenofovir, and pegylated interferon in patients with CHB.Methods: A Markov model was developed to evaluate the costs and benefits of antivirals in a cohort of patients with CHB (hepatitis B e antigen [HBeAg]-positive and HBeAg-negative) and cirrhosis over a period of 10 years. Different rescue therapies were considered, according to current guidelines. Data on efficacy and changes in quality of life were derived from clinical trials and epidemiological Italian data. Direct costs were assessed from the perspective of the Italian National Health Service.Results: Tenofovir was associated with lower costs and higher efficacy compared with entecavir, telbivudine, and adefovir, as shown by their incremental cost-effectiveness ratios (ICER) per quality-adjusted life-year (QALY) gained: tenofovir €30,959, entecavir €45,971, telbivudine €62,051, and adefovir €82,824. Even following 1 year of pegylated interferon therapy, tenofovir had a more favourable ICER per QALY gained compared with the other rescue options. The analysis of patients with cirrhosis confirms the results obtained with the CHB cohort though with higher ICERs. Sensitivity analyses on the main variables confirm the results of the base case scenario.Conclusion: Within the Italian health care system, in patients with CHB, tenofovir is a cost-effective strategy compared with other available therapies. Public health care authorities would benefit from mathematical models designed to estimate the future burden of CHB infection together with the impact of treatment and drug resistance.Keywords: chronic hepatitis B, Markov model, cost-effectiveness, lamivudine, adefovir, telbivudine, entecavir, tenofovir, pegylated interferon